Serological Markers to Assess Liver Fibrosis and Their Roles - Beom Kyung Kim (The Korean Journal of Gastroenterology)
Chronic liver disease is a significant public health issue worldwide, with the degree of liver fibrosis and its progression significantly influencing the treatment and prognosis. A liver biopsy is the standard diagnostic method, but it is invasive and presents various issues. Therefore, numerous non-invasive diagnostic methods have been developed. Serum markers are categorized into indirect markers, which reflect liver damage, inflammation, or functional changes, and direct markers, which measure the components released into the bloodstream during fibrosis. In addition, various kinds of formulas that combined direct/indirect markers and demographic variables were developed and validated with encouraging outcomes. Nevertheless, despite their convenience, serum indicators require cautious interpretation because they are affected by a number of factors. More research will be needed to determine if the clinical course of chronic liver disease under a disease-specific treatment could be monitored appropriately using serological markers.